2005
DOI: 10.1111/j.1548-2456.2005.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Democracy: Reforming the Laws on Women's Rights in Chile, 1990–2002

Abstract: This article evaluates 38 bills seeking to expand women's rights in Chile and finds that the successful ones often originated with the Executive National Women's Ministry (SERNAM), did not threaten existing definitions of gender roles, and did not require economic redistribution. These factors (plus the considerable influence of the Catholic Church) correlate in important ways, and tend to constrain political actors in ways not apparent from an examination of institutional roles or ideological identity alone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
15
0
3
Order By: Relevance
“…In addition, it does not illuminate why the same policies (e.g., paid maternity leave) can be controversial in one context (such as the U.S.) but not in another (such as Norway). Blofield and Haas (2005) distinguish between rights-and role-based policies, and those that promote redistribution and threaten class privileges and those that do not, in their study of women's rights legislation in Chile. In a recent book, Casimiro et al (2009) note that in Africa, policies promoting women's equality in the public sphere of state and market have been easier to achieve than those concerning women's rights in the private sphere of home and family.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it does not illuminate why the same policies (e.g., paid maternity leave) can be controversial in one context (such as the U.S.) but not in another (such as Norway). Blofield and Haas (2005) distinguish between rights-and role-based policies, and those that promote redistribution and threaten class privileges and those that do not, in their study of women's rights legislation in Chile. In a recent book, Casimiro et al (2009) note that in Africa, policies promoting women's equality in the public sphere of state and market have been easier to achieve than those concerning women's rights in the private sphere of home and family.…”
Section: Resultsmentioning
confidence: 99%
“…Other aspects of Chilean institutions might lead one to expect more sweeping change. Another institutional vestige of the authoritarian period is a preponderance of executive power, in which legislative proposals emanating from the president are very likely to pass and Congress tends to be weak (Siavelis 2000;Blofield and Haas 2005). Chilean presidents have important powers over Congress, including the ability to introduce legislation directly, control the congressional agenda, assign leadership posts in Congress, and channel public sentiment from a position of greater leadership than congress members possess.…”
Section: Chilean Postretrenchment Politicsmentioning
confidence: 99%
“…However, this is perhaps not surprising given the broader failure within Chile to address gender inequalities and challenge gendered roles and responsibilities (Molina, 1998). In their analysis of 38 proposed parliamentary bills aimed at expanding women’s rights in Chile, Blofield and Haas (2005) found that only those that neither threatened existing gender roles nor required economic re‐distribution were successful. This reflects the inherently conservative nature of Chile and highlights the importance of the Catholic Church in policy making.…”
Section: Reinforcing Gender Roles and Responsibilities In Health Carementioning
confidence: 99%